Ответ:
[tex](a-c) (2b-c)(a+2b)[/tex]
Объяснение:
[tex]2a^2b + 4ab^2 - a^2c + ac^2 -4b^2c + 2bc^2 - 4abc=[/tex]
[tex]2a^2b - 2abc - 2abc+ 2bc^2 - a^2c+ ac^2 + 4ab^2 -4b^2c=[/tex]
[tex]2ab(a-c) - 2bc(a-c) -ac(a-c) + 4b^2(a-c)=[/tex]
[tex](a-c)(2ab-2bc-ac+4b^2)=[/tex]
[tex](a-c)(2ab-ac+4b^2-2bc)=[/tex]
[tex](a-c) \left(a(2b-c)+2b(2b-c)\right)=[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex](a-c) (2b-c)(a+2b)[/tex]
Объяснение:
[tex]2a^2b + 4ab^2 - a^2c + ac^2 -4b^2c + 2bc^2 - 4abc=[/tex]
[tex]2a^2b - 2abc - 2abc+ 2bc^2 - a^2c+ ac^2 + 4ab^2 -4b^2c=[/tex]
[tex]2ab(a-c) - 2bc(a-c) -ac(a-c) + 4b^2(a-c)=[/tex]
[tex](a-c)(2ab-2bc-ac+4b^2)=[/tex]
[tex](a-c)(2ab-ac+4b^2-2bc)=[/tex]
[tex](a-c) \left(a(2b-c)+2b(2b-c)\right)=[/tex]
[tex](a-c) (2b-c)(a+2b)[/tex]